Participatory Branding and Packaging Assistance for PKK Products in Wanakaya Village - Dikky Himawan; Shofi; Nok Luvita Dewi (PT. Berkah Digital Teknologi, 2023)
This community service program addressed weak product identity and basic packaging among members of the Family Welfare Empowerment group (PKK) in Wanakaya Village, Gunung Jati District, Cirebon Regency. The program aimed to develop a practical and affordable visual identity, improve packaging consistency, and strengthen participants’ understanding of branding without making unsupported claims about sales or income. Fifteen active PKK members involved in local food production participated in three sequential phases: a baseline review of existing products, a branding and packaging workshop followed by participatory design, and a qualitative evaluation of the resulting prototype. Data were drawn from product observation, participant feedback, program documentation, and informal comments from local consumers and vendors, then organized thematically and summarized through a SWOT analysis. The program produced a shared “Bubur Bayi” logo and label sheet, together with a labeled transparent-container prototype. Compared with the initial unbranded presentation, the output provided clearer product identification and more consistent visual presentation. Participants and local respondents considered the prototype more recognizable and attractive, although concerns remained regarding printing cost, packaging material, label size, product information, and the balance between local identity and contemporary aesthetics. Because the original program records did not contain numerical pre–post scores, evaluator counts, or longitudinal sales data, the verified outcome is limited to visual-identity development and perceived packaging improvement. Continued mentoring, complete label information, and market testing are recommended before wider commercialization.